Complex training for power development: Practical applications for program design - Lim, J. J. H.; Barley, C. (Strength and Conditioning Journal, 2016)
The short-term gains in power and rate of force development after maximal or high-intensity dynamic exercises are thought to result from postactivation potentiation (PAP). The major factors affecting pap utilization are the optimal intracomplex recovery, training status, and strength levels of the athletes. Studies have shown that with the ideal combination of moderately highly trained athletes and adequate intracomplex recovery, it is possible to effectively implement complex training for power development. This paper looks to review the current literature of studies investigating the chronic adaptations of PAP in a training cycle and recommend an effective and practical complex training program.